Shusterman's pragmatism : between literature and somaesthetics - Koczanowicz, Dorota.; Małecki, Wojciech. (Value Inquiry Book Series, 2012)
This book is the first essay collection on Richard Shusterman, the foremost representative of contemporary pragmatist aesthetics, a philosopher whose books have been translated into more than fifteen languages. The 12 essays, which cover the wide-ranging scope of Shusterman's pragmatist thought, divide into three sections: Literary Theory and Philosophy of Art; Epistemology, Metaphysics, Ethics, and Politics; and Somaesthetics. Written by an international group of authors from different philosophical perspectives, the book's essays not only provide a good introduction to Shusterman's innovative pragmatist theories, but show their useful applications to important and controversial topics in philosophy, politics, religious and gender studies, the arts, and somaesthetics. The book also includes two new texts by Shusterman: an introductory essay in which he explains the trajectory of his intellectual development and a detailed response to the other contributors, which closes the book.